Finite element simulation of physical systems in augmented reality. (November 2020) - Logg, Anders; Lundholm, Carl; Nordaas, Magne
Highlights: Augmented reality app for interactive physics simulation in real-world surroundings. Time-dependent advection-diffusion equation is solved with FEM. All computations are done on the Microsoft HoloLens. Potential usage in HVAC-simulations and education. Abstract: We present a system for immersive and interactive physics simulation in augmented reality, implemented as an application on the Microsoft HoloLens. The system allows a user to simulate physical phenomena in real-world geometries by scanning the surroundings and automatically creating a finite element discretization (mesh). The system also provides a user interface based on voice commands for specification of boundary conditions and source terms, and for immersive visualization of simulation results. All computations are carried out on the HoloLens. The current implementation, named HoloFEM, demonstrates the application of augmented reality simulation for the time-dependent advection–diffusion equation. In the current work, we consider a simplified model problem with simplified parameters and data. The model is however still conceptually applicable to the simulation of indoor climate (temperature and air quality), which has implications for interactive HVAC (heating, ventilation, and air conditioning) simulation.